VD_FINDINFO Décision / 2013 / 250 vom 10. Dezember 2012 - VD Tribunal cantonal (2012)
RETRAITVOIE DE DROIT, DEMANDE ADRESSÉE À L'AUTORITÉ, DISPENSE, TÉMOIN | 169 CPP (CH), 393 al. 1 let. b CPP (CH), 428 al. 1 CPP (CH)